Chemistry and antioxidant activity of essential oil and oleoresins of black caraway (Carum bulbocastanum) fruits: Part 69 - Singh Kapoor, Inder Pal (2010)
BACKGROUND: The present study describes the chemical analysis of the essential oil and oleoresins from caraway, which have been studied by using GC-MS. The paper also explains the importance of the extracted oil and oleoresins in the antioxidant activities of target plant species. RESULTS: GC-MS analysis of caraway essential oil showed 51 compounds representing about 96.6% of the total weight. The major components were dillapiole (44.6%), germacrene-β (14.1%), nothoapiole (8.3%), and β-selinene (6.8%), along with many other components in minor amounts. Major components in ethyl acetate and iso-octane oleoresins are dillapiole, nothoapiole and germacrene-β, whereas in ethanol oleoresin contains dillapiole (25%), sitosterol (21.3%) stigmasterol (9.5%) and nothoapiole (8.1%). The antioxidant activity was evaluated by various antioxidant assays such as peroxide, thiobarbituric acid and p-anisidine values. These experiments were further supported by other complementary antioxidant assays such as ferric thiocyanate method in linoleic acid system, reducing power, and scavenging effects on 1,1′-diphenyl-2-picrylhydrazyl (DPPH). Both the caraway volatile oil and its oleoresins showed strong antioxidant activity in comparison with butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT). CONCLUSION: This study provides additional information about the chemistry and antioxidant activity of caraway. Hence, caraway may be used as natural food preservatives.